PENGELOLAAN KEUANGAN DESA BERBASIS APLIKASI SISKEUDE DI DESA KEBUN DURIAN KABUPATEN KAMPAR - Rahayu Wildiani; Zulkarnaini ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The existence of Law No. 6 of 2014 gives villages the opportunity to manage their own governance, including managing village finances. Village financial management itself consists of five stages, namely the planning, implementation, administration, reporting, and accountability stages. To support effective and efficient village financial management, the government through the Finance and Development Supervisory Agency (BPKP) and the Directorate General of Village Government Development, the Ministry of Home Affairs, collaborated to create an application called the Village Financial System (Siskeudes). Where Siskeudes is designed and refers to Permendagri Number 20 of 2018 concerning Village Financial Management. This study aims to determine the village financial management process based on the Village Financial System (Siskeudes) application in Kebun Durian Village, Kampar Regency. The method used in this research is descriptive qualitative, in which the researcher describes events or incidents in the field. The results of this study indicate that village financial management based on the Siskeudes application in Kebun Durian village is in accordance with Permendagri Number 20 of 2018 concerning Village Financial Management. Where all stages starting from planning, implementation, administration, reporting, and accountability have been carried out properly. However, there are still obstacles in the process, namely inadequate human resources, complete facilities and lack of training regarding the Siskeudes application. This study concludes that the Siskeudes application is very helpful for village officials in managing finances and making accountability reports, even though there are several obstacles in the process of operating it. and it is hoped that the village government can overcome some of these obstacles. Keywords: Village Financial Management, Siskeudes